Effect of temperature on the durability of systems for strengthening of concrete structures - Vaz, Nelson (2005)
Nowadays, there is a need in solving problems about the reinforcement of concrete structures. The external reinforcement of concrete with composite materials is a technique that has acquired more and more potential. The bond between reinforcement and support is usually made with epoxy adhesives. However, it is in this part that the integrity of the system can be affected, namely by exposure to high temperatures, amongst various other reasons. In order to study the behaviour of the external reinforcement with the increase of air temperature, several beams were prepared and strengthened with CFRP laminates. After cyclical thermal exposition of 25 days, with maximum temperatures of 20°C, 40°C, 60°C and 80°C, the beams were subjected to bending tests. The results demonstrated that the improvement achieved with the reinforcement, disappears with the increase of the environment's temperature. The thermal resistance of this strengthened system is not very high, thus special needs to be taken into account when applied in warm locations.